Gender Differences in the Effects of BMI on School Bullying and Victimization in China: Comparing Normal Weight, Underweight and Overweight Secondary School Students - Yang Xie; Xiying Wang; Xiaotao Wang; Liu Liu (MDPI AG, 2022)
Weight-related school bullying and victimization have become important public health issues among adolescents around the world. This study aims to examine gender differences in the effects of Body Mass Index (BMI) on school bullying and victimization among secondary school students. This study conducted a survey among 2849 adolescents-1393 girls (48.9%) and 1456 boys (51.1%). The students were between 12 and 18 years of age and were recruited from ten secondary schools in 2019 in Suqian City in China. The study showed that overweight boys were more likely to bully others and be bullied by peers compared to normal weight boys. In contrast, overweight girls reported less bullying than normal-weight girls. No significant relationship was found between overweight and victimization among female students. The implications for comprehensive sexuality education practices are also discussed.